What Makes the Headlines: A Five-Year Analysis of the Front Page of the 'Ghanaian Times' - Kwaku Baah-Acheamfour; Judith Lamptey-George (Journal of Arts, Humanities and Social Science)
This study aimed to identify the various story types featured on the front pages of the ‘Ghanaian Times’ newspaper. Utilising the gatekeeping and framing theories, the study aimed to establish the dominant story types, news actors, and story settings. The variables were based on the fact that the ‘Ghanaian Times’, a state-owned print media with a constitutional obligation to offer equal facilities and opportunities to all to express divergent views and opinions, would do just that. That was not the case, as the data results showed a skewed coverage for political news, the elite, and urban settings. The newspaper, in the exercise of its gatekeeping function, ended up with unfavourable coverage towards rural folks, the masses, and even other non-political news. The study also adopted the qualitative approach and content analysis design, with thematic analysis used in handling the data, especially in coming up with the themes and corresponding frames about the story types, news actors, themes, and tone of the news stories. With the skewed representation at its premium front page, the editors must stop prioritizing profit over impact, thereby ensuring diversity of content to reflect the interests of the masses, rural areas, and non-political consumers.